IPv6 communication capability index and its application in end-to-end carrier network - Yangchun LI; Weiwei FENG (Dianxin kexue)
The traditional way was used to qualitatively describe the IPv6 communication capabilities for end-to-end carrier grade network with many old devices.By introducing concepts of IPv6 communication events,IPv6 communication capability index,the algorithms were presented to calculate the IPv6 communication capability index for single node,node set,single path,multi-path and end-to-end network.These algorithms were also used to analyze and evaluate the IPv6 communication capability for end-to-end carrier grade network.